Elevated Expression of the Long Noncoding RNA IFNG-AS1 in the Peripheral Blood from Patients with Rheumatoid Arthritis - Huiyong Peng; Shuting Ren; Yingzhao Liu; Huimin Zhou; Xinyi Tang; Jun Yang; Jie Tian; Ping Xu; Huaxi Xu; Shengjun Wang (Journal of Immunology Research, 2020)
Long noncoding RNAs (lncRNAs) have been increasingly recognized as key immune molecules that participate in the pathogenesis of autoimmune diseases. Previous studies have demonstrated that the lncRNA Ifng-AS1, a key scaffold that contributes to the transcription of IFN-γ, depends on T-bet for active transcription in Th1 cells. However, the effect of its human ortholog, IFNG-AS1, on the pathogenesis of rheumatoid arthritis (RA) remains unclear. In this study, we found that the transcript level of lncRNA IFNG-AS1 was increased in the peripheral blood of RA patients. IFNG, as a target gene of IFNG-AS1, was overexpressed and positively correlated with the transcript level of IFNG-AS1 in the RA patients. Our data also showed that the transcript level of T-bet was upregulated and positively correlated with IFNG-AS1 expression. T-bet regulated the transcription of IFNG-AS1 in human CD4+ T cells in vitro. Furthermore, strong positive correlations were observed between the increased transcript level of IFNG-AS1 and the serum level of rheumatoid factor, the erythrocyte sedimentation rate, and the C-reactive protein in RA patients, and patients positive for anticyclic citrullinated peptide antibodies had increased levels of IFNG-AS1. Finally, receiver operating characteristic (ROC) curve analysis suggested that IFNG-AS1 might be a potential biomarker of RA. Taken together, our findings indicated that IFNG-AS1, guided by T-bet, is augmented in the peripheral blood of RA patients and may play a critical role in the pathogenesis of RA by regulating the expression of IFNG.